IMMUNOMODULATORY ACTIVITY OF CHATURTHAMALAKA RASAYANA: AN EXPERIMENTAL EVALUATION (International Journal of Ayurveda and Pharma Research, 2019)
Triphala, a simple combination of Amalaki, Haritaki and Bibhitaki, have proven antioxidant and immunomodulatory activities. But, work on Chaturthamalaka Rasayana, containing Triphala, under four alternate combinations, was not found reported yet. For this, a study was conducted to evaluate the effect of different four combinations under Chaturthamalaka Rasayana on leucocytes and immunoglobulin with special reference to immunomodulatory activity in albino wistar rat model. Four combinations of test drugs were prepared as per classical textual guidelines mentioned in Charaka Samhita. 36 wistar strain albino rats were used in the study. Immunosuppression done by Cyclophosphamide which induced neutropenia. Total leucocyte count (TLC) (cells/mm3), % Neutrophil count and Serum immunoglobulin level (in ZST units) were parameters used to evaluate. All the data were collected and analysed using paired‘t’ test and one way ANOVA test, followed by Dunnett’s multiple comparison ‘t’ test. All the test formulations showed much better effect in comparison with the improvement noted in control group, as a cytoprotective agent. However, with respect to immunostimulation, the control group showed better effect in comparison to the test formulation. Chaturthamalaka Rasayana possesses significant cytoprotective activity and moderate immunostimulant activity. Among the four combinations, all test samples were found effective in immunosuppressive rats. Test sample IV containing Amalaki, Haritaki and Bibhitaki found more potent than or as similar as response in comparison of standard group (Levamisole). Chaturthamalaka Rasayana might be consider as a cost effective and adulteration free alternative formulation over used of costly Chyavanaprasha Avaleha.